New meanings for the Córdoba reform: University of Nariño case - Erazo Coral, María Elena (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The purpose of this article is to reflect on the new meanings that the Cordoba reform takes in the 21st Century, because today, as yesterday, it is necessary for the student and teacher movement to embrace this new "university idea" in order to face the neoliberal policies on education proposed by centers of power through the World Bank or the OECD. This is the case of the student and professorial movement in the University of Nariño, which undertakes a struggle to consolidate a University at the service of men and women in the Colombian south-west and not at the service of the market and capital. For this purpose, they have created conditions where the principles of autonomy and democracy, achieved in the Córdoba reform, are lived in a real way in a specific space called; the University Assembly. This paper is the result of a research work entitled "The reforms of the University of Nariño, 1972 and 2009", financed by this Institution. The methodology is based on the proposal of Carlos Rincon Bolivar "the non- simultaneity of the simultaneous" that seeks to analyze and understand the national and international historical processes, but it especially focuses on all the particularities of these processes in specific contexts, thus contributing to the regional history.